Design and Fabricate the Prototype of a Motorized Cutter for Harvesting Palm Fruit - Zamzuri, Hamedon; Siti Haryani, Tomadi; M. M., Noor; M. N. O., Zahid (2008)
A new harvesting pole, specifically developed for palms trees, was designed, developed and tested. It comprises three sections, the engine, extension and replaceable sickle/chopper, which were joined through an aluminum pole. The pole can be adjusted to certain length to reach different height of tree. It is built using standard circular rod with cross section diameters of 50 mm. This newly invented replaceable sickle/chopper pole has been designed based on the ordinary sickle and chopper widely used in Malaysia palm estates. This innovation introduced new mechanism concept of small chain saw engine as a source of mechanical force to cut the frond and fruit bunch. The replaceable system was designed and located at the end of the pole for easily detachable manually. While the threaded steel used to link the engine systems and replaceable sickle/chopper system can be easily replace for higher tree.